Pemberdayaan dan Pengabdian Masyarakat dalam Pengurusan Sekolah dan Memperluaskan Perniagaan di Kampung Bukitberangan, Thailand - Dolohkade, Miss Firdaus; Jeh-asae, Miss Nuseema; Tripalupi , Ramadhani Irma; Nurlatifah, Eva (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
In the socialization process, activities were carried out online with the school to collect data and find out problems and needs then review the needs in the community and it was found that the school needed energy to manage or rearrange student data and the community really needed help from the point of looking for income. After the socialization was carried out and several problems were noted, I formed or organized several activities and gave a little enlightenment about online business to the local community to make it easier for them to develop more local products or homemade products that were processed by the locals themselves. Furthermore, in the implementation, the author comes to the school to help the school in several ways, and for the local community, the author provides teaching instructions about product packaging and how to market the product on social media. After that, the author creates an account to promote and market homemade products that are made available on social media.